Evaluating the value and impact of the Victorian Audit of Surgical Mortality. Issue 10 (16th July 2013) - Retegan, Claudia; Russell, Colin; Harris, Darren; Andrianopoulos, Nick; Beiles, C. Barry
Abstract Introduction Since the Victorian Audit of Surgical Mortality (VASM) commenced in 2007, 95% of Victorian Fellows have agreed to participate and have provided data on the deaths of patients receiving surgical care. All public, and the majority of private, hospitals involved in the delivery of surgical services in Victoria have been submitting data on deaths associated with surgery. De‐identified reports on this data are distributed in regular annual reports and case note review booklets. Although informal feedback on the perceived value of the audit was encouraging, a formal review of all aspects of the audit was felt necessary. Methods An independent formal review of VASM governance, documentation, datasets and data analysis was performed, in addition to a survey of 257 individuals (surgeons and other stakeholders) on the perceived impact of VASM. Results The review confirmed increasing participation and acceptance by surgeons since the inception of the project. Governance mechanisms were found to be effective and acknowledged by stakeholders and collaborators. Robust participation rates have been achieved, and stakeholders were generally satisfied with the quality of feedback. Suggestions for improvement were provided by some surgeons and hospitals. Conclusion External review of VASM processes and procedures confirmed that the audit was operating effectively, with robust quality control and achieving the trust of stakeholders. The educational value of the audit to the surgical community was acknowledged and areas for future improvement have been identified.